2018
DOI: 10.1021/acs.orglett.8b01697
|View full text |Cite|
|
Sign up to set email alerts
|

Enantioselective Synthesis of 5-Alkylated Thiazolidinones via Palladium-Catalyzed Asymmetric Allylic C–H Alkylations of 1,4-Pentadienes with 5H-Thiazol-4-ones

Abstract: A palladium-catalyzed, enantioselective allylic C-H alkylation of 1,4-pentadienes with 5 H-thiazol-4-ones has been developed. Under the cooperative catalysis of a palladium complex of chiral phosphoramidite ligand and an achiral Brønsted acid, a broad range of substituted 5 H-thiazol-4-ones bearing sulfur-containing tertiary chiral centers were accessed from the allylic C-H alkylation in high levels of yields and enantioselectivities. Alkyl and aryl 1,4-pentadienes led to linear and branched allylation product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…By means of DFT calculations, we identified that the geometry and coordination pattern of nucleophiles lead to different bond‐forming transition states and thereby determine the Z / E selectivites and regioselectivities (Scheme B) . For instance, the allylic C−H alkylation of 1,4‐dienes with pyrazol‐5‐ones and 5‐aryl‐substituted thiazol‐4(5 H )‐ones greatly favor branched E ‐dienyl products via the inner‐sphere transition‐state TS1 , while branched Z ‐dienyl products were obtained via the inner‐sphere TS2 upon using azlactones as nucleophiles . In contrast, the outer‐sphere TS3 became dominant and linear E ‐dienyl products were given when 5‐alkyl‐substituted thiazol‐4(5 H )‐ones were used .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By means of DFT calculations, we identified that the geometry and coordination pattern of nucleophiles lead to different bond‐forming transition states and thereby determine the Z / E selectivites and regioselectivities (Scheme B) . For instance, the allylic C−H alkylation of 1,4‐dienes with pyrazol‐5‐ones and 5‐aryl‐substituted thiazol‐4(5 H )‐ones greatly favor branched E ‐dienyl products via the inner‐sphere transition‐state TS1 , while branched Z ‐dienyl products were obtained via the inner‐sphere TS2 upon using azlactones as nucleophiles . In contrast, the outer‐sphere TS3 became dominant and linear E ‐dienyl products were given when 5‐alkyl‐substituted thiazol‐4(5 H )‐ones were used .…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the allylic C−H alkylation of 1,4‐dienes with pyrazol‐5‐ones and 5‐aryl‐substituted thiazol‐4(5 H )‐ones greatly favor branched E ‐dienyl products via the inner‐sphere transition‐state TS1 , while branched Z ‐dienyl products were obtained via the inner‐sphere TS2 upon using azlactones as nucleophiles . In contrast, the outer‐sphere TS3 became dominant and linear E ‐dienyl products were given when 5‐alkyl‐substituted thiazol‐4(5 H )‐ones were used . Inspired by the inner‐sphere attack mechanism (inner‐sphere TS4 ), we hypothesized that the introduction of a proper coordination site to the nucleophile might be possible to modulate the regioselection of allylic C−H alkylation of 1,4‐dienes to preferentially generate C3‐branched products.…”
Section: Methodsmentioning
confidence: 99%
“…By means of DFT calculations, we identified that the geometry and coordination pattern of nucleophiles lead to different bond‐forming transition states and thereby determine the Z / E selectivites and regioselectivities (Scheme B) . For instance, the allylic C−H alkylation of 1,4‐dienes with pyrazol‐5‐ones and 5‐aryl‐substituted thiazol‐4(5 H )‐ones greatly favor branched E ‐dienyl products via the inner‐sphere transition‐state TS1 , while branched Z ‐dienyl products were obtained via the inner‐sphere TS2 upon using azlactones as nucleophiles . In contrast, the outer‐sphere TS3 became dominant and linear E ‐dienyl products were given when 5‐alkyl‐substituted thiazol‐4(5 H )‐ones were used .…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the allylic C−H alkylation of 1,4‐dienes with pyrazol‐5‐ones and 5‐aryl‐substituted thiazol‐4(5 H )‐ones greatly favor branched E ‐dienyl products via the inner‐sphere transition‐state TS1 , while branched Z ‐dienyl products were obtained via the inner‐sphere TS2 upon using azlactones as nucleophiles . In contrast, the outer‐sphere TS3 became dominant and linear E ‐dienyl products were given when 5‐alkyl‐substituted thiazol‐4(5 H )‐ones were used . Inspired by the inner‐sphere attack mechanism (inner‐sphere TS4 ), we hypothesized that the introduction of a proper coordination site to the nucleophile might be possible to modulate the regioselection of allylic C−H alkylation of 1,4‐dienes to preferentially generate C3‐branched products.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] Enantioselective functionalization of allylic C-H bonds constitutes an ideal approach to introduce allyl groups to chiral molecules and attracts researchers' interests. 13 Several catalytic enantioselective protocols of allylic C-H functionalization via an electrophilic allyl-metal intermediate promoted by a Pd [14][15][16][17][18][19][20][21][22][23][24][25][26][27] or Rh 28,29 complex have been developed (Figure 1a). More recently, enantioselective allylic C-H functionalization via allyl radicals through metal-catalyzed or photocatalyzed C-H bond cleavage has been revealed ( Figure 1a).…”
Section: Introductionmentioning
confidence: 99%